An Investigation of the Development and Implementation of Teacher's Licensing in Saudi Arabia Based on Local Stakeholders' Perceptions, Compared to International and Regional Practices - HAMEEDADIN, AMAL ABDULLAH (2023)
Globally, there has been considerable concern about education reform to prepare future citizens for the unpredictable demand for labour. It is widely agreed among stakeholders in the education industry that teachers are central to the learning and teaching processes. However, promoting teacher quality concerns leaders in the education sector, and significant efforts to raise teacher quality are paramount to government leaders. At this level, teacher licensure has been introduced to measure teachers' performance and prepare them for the education industry. Saudi Arabia is moving steadily and swiftly toward Vision 2030 to prepare the young generation to pursue advanced studies. Accordingly, the Educational & Training Evaluation Commission (ETEC) has teamed up with the Ministry of Education in Saudi Arabia to update and raise the 'Teacher Licensure Programme' bar. The exploratory sequential mixed method aimed to investigate the development and implementation of the 2019 teacher licensure programme in Saudi Arabia. The study was based on reviewing policies of best practices and stakeholders' perceptions. During the study, a model framework was proposed to the relevant stakeholders and educational leaders aligned with Gulf culture and international standards. The study consisted of three stages. In the first stage, six policies were reviewed and analyzed to compare international, regional, and local licensures and collected secondary data from official documents. During this stage, the researcher conducted an in-depth interview with an ETEC policymaker, who provided insight and enlightened the researcher regarding the programme's foundation. Stage two delved into a large portion of stakeholders. The study collected quantitative data from 306 teachers from public schools who shared their experiences and perceptions of the licensing exam through an online survey. The last stage collected qualitative data through a school leaders' questionnaire and a policymaker interview. The qualitative data investigated leaders' perspectives on the teachers' data findings and the implementation of licensing in schools based on principals, supervisors, and a policymaker's point of view. Stage one findings were linked to international and regional practices. A comparative study revealed a lack of career development at the college level and during in-service training in Saudi Arabia. Furthermore, there is a need for a standardized teacher evaluation system that includes constructive feedback and reflection. Based on stage two findings, teachers expressed negative views regarding the current licensing programme. In addition, phase three findings followed up on teachers' perceptions from the perspective of school leaders and policymakers. This study filled a critical gap in the theoretical field of teacher licensing in the Gulf Region. Additionally, the research suggested a flexible framework based on the best practices and the perceptions and experiences of the stakeholders. The framework asserted that the licensing examination is one of several teacher evaluation methods.